UPAYA MENINGKATKAN PRESTASI BELAJAR IPA PADA SISWA SMP MELALUI PENERAPAN MODEL PEMBELAJARAN COOPERATIVE - Elisabet Br. Gurusinga; Ernalem Tarigan (Center for Research and Community Service (LPPM) University of Abulyatama, 2021)
This study aims to determine the improvement of student achievement in class VII on the material of vibration, waves and sound through the application of the Cooperative Script learning model. This research is a class action research conducted in 2 cycles. Each cycle includes planning, implementation, observation and reflection. The subjects of this class action research were students of class VIII even semester of SMP Private Gema Bukit Barisan Tanjung Morawa, totaling 32 people. While the object is the Cooperative Script learning model. From the research conducted by examining the initial conditions of students as measured by written tests and the results of classroom action research with 2 cycles, it was seen that there was an increase in learning outcomes achieved by students in mastering the material of vibration, waves and sound. Based on the data analysis, it can be concluded that in cycle 1 the number of students who have not completed as many as 24 people or 75% and only 8 students or 25% have completed, and in cycle 2 students who have completed the material on vibrations, waves and sound increased to 29 people or 90 ,63% and 3 people who have not been completed or 9.37%. This is influenced by teachers and students who are accustomed to using cooperative script learning models so that students become active in receiving lessons